Resilience of Urban Poor Community to COVID-19 Disaster in Panjang, Bandar Lampung, Indonesia - Hidayati, Dewi Ayu; ., Yulianto; Utoyo, Bambang; Muhassin, Mohammad (International Journal of Membrane Science and Technology, 2023)
This study aims to explore the resilience capacity of the urban poor in Panjang subdistrict, Bandar Lampung Indonesia in dealing with the COVID-19 disaster in terms of preparedness, adaptation and mitigation capacities. This is a kind of descriptive qualitative research employing in-depth interviews and observation as data collecting techniques. The data analysis comprised data reduction, data presentation, and drawing conclusions. The findings indicated that community resilience to COVID-19 was marked by the capacity for preparedness, adaptation and mitigation involving various components of society, such as civil servants, community leaders, religious leaders, youth leaders and the COVID-19 task force. These components serve as a role model for the urban poor and have a major influence on their efforts to survive during a pandemic. The findings of this research highly emphasize the importance of collaboration between elements of society to increase their resilience capacity in dealing with the COVID-19 disaster and make a real contribution to achieving health development during a pandemic.